2014
DOI: 10.1002/2013jd021340
|View full text |Cite
|
Sign up to set email alerts
|

Ozone pollution: What can we see from space? A case study

Abstract: Due to its impact on environment, tropospheric ozone received particular attention since several decades. Ground-based networks associated with regional chemical transport models are used to monitor and forecast surface ozone concentrations, but coverage, representativeness, and accuracy issues remain important. Recent satellite observations have demonstrated the capacity to probe tropospheric ozone, but there has been no explicit attempt to quantify their ability to measure ozone pollution near ground. We pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…For PROFOZ, early versions were partially evaluated against ozonesonde, aircraft, MLS, surface measurements, model simulations, and tropospheric ozone derivations from other methods (Pittman et al, 2009;Liu et al, 2010bLiu et al, , 2013aZhang et al, 2010;Walker et al, 2010;Tarasick et al, 2010;Sellitto et al, 2011;Bak et al, 2013aBak et al, , b, 2015Foret et al, 2014;Ziemke et al, 2014). The analyses generally showed good agreement with other correlative data but revealed limited sensitivity to ozone in the lower troposphere and near the surface.…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%
“…For PROFOZ, early versions were partially evaluated against ozonesonde, aircraft, MLS, surface measurements, model simulations, and tropospheric ozone derivations from other methods (Pittman et al, 2009;Liu et al, 2010bLiu et al, , 2013aZhang et al, 2010;Walker et al, 2010;Tarasick et al, 2010;Sellitto et al, 2011;Bak et al, 2013aBak et al, , b, 2015Foret et al, 2014;Ziemke et al, 2014). The analyses generally showed good agreement with other correlative data but revealed limited sensitivity to ozone in the lower troposphere and near the surface.…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%
“…We analyse LT and LMT ozone observations for a typical ozone pollution outbreak over Europe during summer. It is a moderate ozone event, mainly occurring on 19 and 20 August 2009 (also analysed by Sellitto et al, 2013, andForet et al, 2013). Surface ozone concentrations occasionally reached 90 ppb (the ozone information threshold; e.g.…”
Section: Lowermost Tropospheric Ozone Observed By Iasi + Gome-2mentioning
confidence: 99%
“…Liu et al, 2010) and TIR sensors are particularly sensitive to tropospheric ozone, down to the lower troposphere (below 6 km altitude; Eremenko et al, 2008). However, it has been shown that when using space-borne observations from one spectral domain (either TIR or UV), only ozone down to 3-4 km altitude at the lowest may be observed with adequate vertical sensitivity (Foret et al, 2014). Recent studies combine the information on ozone distribution from radiance measurements of different spectral domains to enhance sensitivity in the LMT.…”
mentioning
confidence: 99%